P192 Clinical effectiveness of non-invasive ventilation in patients with Motor Neuron Disease. (12th November 2015) - Freeman, D; Jothieswaran, A; Mascareno, M; Chaudhry, N; Bokhari, S; Felton, TW; Bentley, AM
Abstract : Introduction and objectives: The use of long term non-invasive ventilation (NIV) for type II respiratory failure caused by Motor Neuron Disease (MND) is well recognised. In patients with MND and good bulbar function, NIV has been shown to improve survival and quality of life. 1 NIV use in patients with MND has increased since the publication of the National institute of Clinical Health Excellence guidelines in July 2010. Our objective was to identify the clinical effectiveness of NIV in all patients with MND referred to a large tertiary referral teaching hospital service. Methods: All patients with MND established on NIV were identified retrospectively from a clinical database. Patients were excluded from the analysis if there was another diagnosis as the main indication for establishing NIV. All patient data was anonymised. A Kaplan-Meier survival analysis was performed and the median survival was estimated. Results: 222 patients with MND established on NIV were identified. The median age was 64 years (range 19–90 years). One hundred and forty patients (63%) were male and 82 (37%) female. The median survival was 436 days on NIV. The Kaplan-Meier survival curve is shown below. Conclusion: A median survival of 436 days compares favourably with the median survival of 219 days identified in patients with MND receiving NIV in the trial by Bourke et al . Our patient cohort included patients with both limb onset and bulbar onset forms of the disease. The impact on survival may, in part, be due to NIV but overall improvements in medical care, supporting adequate nutrition and assisted cough techniques in a specialist centre will have contributed. Reference: 1 Bourke SC, et al . Effects of non-invasive ventilation on survival and quality of life in patients with amyotrophic lateral sclerosis: a randomised controlled trial. Lancet Neurol . 2006;5 :140–7